Step by Step in Argentina: Putting Abortion Rights into Practice - Ramos, Silvina (2023)
In December of 2020, the Argentine Congress legalized abortion through 14 weeks, vastly increasing access to abortioncare in the country. The law’s passage followed years of advocacy for abortion rights in Argentina - including mass public and civilsociety mobilization, vocal support from an established pool of abortion providers who offered abortion services under specific legalexceptions prior to the new law, and the growth of community groups such as the Socorristas en Red who provide support for people toself-manage abortions. Aided by ample political will, the number of health facilities offering services increased substantially after thelaw was passed, and the public visibility around the law has helped assure people seeking abortion that it is their right. Proyecto miraris an initiative focused on both gathering and using qualitative and quantitative data to inform stakeholders about the progress andobstacles of the law’s implementation. In this review, we present an overall summary of the first two years of implementation of theabortion law in Argentina based on proyecto mirar data and contextualized through the historical processes that have contributed to thelaw’s passage and application. While we see increases in abortion services and improved public perception around abortion rights,inequities in access and quality of care persist throughout the country. Specifically, providers in some regions are well trained, whileothers create obstacles to access, and in some regions health services provide high quality abortion care whereas others providesubstandard care. To be sure, the implementation of public policies does not happen overnight; it requires government support andbacking to tackle obstacles and solve implementation problems. Our findings suggest that when new abortion laws are passed, theymust be supported by civil society and government leaders to ensure that associated policies are well crafted and monitored to ensuresuccessful implementation.